To solve the equation, you can follow these steps:
Step 1: Start by subtracting 4 from both sides of the equation to isolate the fraction term:
2/5x + 4 - 4 = 1/5 - 4
2/5x = 1/5 - 4
Step 2: Simplify the right side of the equation:
2/5x = 1/5 - 20/5
2/5x = -19/5
Step 3: To get rid of the fraction, multiply both sides of the equation by the reciprocal of the fraction's coefficient (5/2):
(5/2)(2/5x) = (5/2)(-19/5)
x = -19/2
So, the solution to the equation is x = -19/2.
2/5x +4 =1/5
11 answers
5/3 - 2x = 1/6
To solve the equation, you can follow these steps:
Step 1: Start by subtracting 5/3 from both sides of the equation to isolate the term with x:
5/3 - 5/3 - 2x = 1/6 - 5/3
-2x = 1/6 - 5/3
Step 2: Simplify the right side of the equation:
-2x = 1/6 - 10/6
-2x = -9/6
Step 3: To get rid of the fraction, multiply both sides of the equation by the reciprocal of the fraction's coefficient (6/(-2)):
(-2/6)(-2x) = (-2/6)(-9/6)
x = 18/12
Step 4: Simplify the result:
x = 3/2
So, the solution to the equation is x = 3/2.
Step 1: Start by subtracting 5/3 from both sides of the equation to isolate the term with x:
5/3 - 5/3 - 2x = 1/6 - 5/3
-2x = 1/6 - 5/3
Step 2: Simplify the right side of the equation:
-2x = 1/6 - 10/6
-2x = -9/6
Step 3: To get rid of the fraction, multiply both sides of the equation by the reciprocal of the fraction's coefficient (6/(-2)):
(-2/6)(-2x) = (-2/6)(-9/6)
x = 18/12
Step 4: Simplify the result:
x = 3/2
So, the solution to the equation is x = 3/2.
not a answer
Apologies for the incorrect response. Let's solve the equation correctly:
To solve 5/3 - 2x = 1/6, you can follow these steps:
Step 1: Start by subtracting 5/3 from both sides of the equation to isolate the term with x:
5/3 - 5/3 - 2x = 1/6 - 5/3
-2x = 1/6 - 5/3
Step 2: To simplify the right side of the equation, find a common denominator. The least common denominator between 6 and 3 is 6. Rewrite the fractions:
-2x = 1/6 - 10/6
Step 3: Combine the fractions on the right side of the equation:
-2x = (1 - 10)/6
-2x = -9/6
Step 4: Simplify the fraction on the right side of the equation:
-2x = -3/2
Step 5: To solve for x, divide both sides of the equation by -2:
x = (-3/2) / (-2)
x = (-3/2) * (-1/2)
x = 3/4
So, the solution to the equation is x = 3/4.
To solve 5/3 - 2x = 1/6, you can follow these steps:
Step 1: Start by subtracting 5/3 from both sides of the equation to isolate the term with x:
5/3 - 5/3 - 2x = 1/6 - 5/3
-2x = 1/6 - 5/3
Step 2: To simplify the right side of the equation, find a common denominator. The least common denominator between 6 and 3 is 6. Rewrite the fractions:
-2x = 1/6 - 10/6
Step 3: Combine the fractions on the right side of the equation:
-2x = (1 - 10)/6
-2x = -9/6
Step 4: Simplify the fraction on the right side of the equation:
-2x = -3/2
Step 5: To solve for x, divide both sides of the equation by -2:
x = (-3/2) / (-2)
x = (-3/2) * (-1/2)
x = 3/4
So, the solution to the equation is x = 3/4.
0.2x - 2.15= -8/27
To solve the equation, you can follow these steps:
Step 1: Start by adding 2.15 to both sides of the equation to eliminate the constant term:
0.2x - 2.15 + 2.15 = -8/27 + 2.15
0.2x = -8/27 + 2.15
Step 2: To simplify the right side of the equation, find a common denominator. The least common denominator between 27 and 1 is 27. Rewrite the fractions:
0.2x = (-8/27) + (2.15 * 27/27)
0.2x = -8/27 + 57.85/27
Step 3: Combine the fractions on the right side of the equation:
0.2x = (-8 + 57.85)/27
0.2x = 49.85/27
Step 4: To solve for x, divide both sides of the equation by 0.2:
x = (49.85/27) / 0.2
x = (49.85/27) * (1/0.2)
x = (49.85/27) * 5
Step 5: Simplify the result:
x ≈ 9.240
Step 1: Start by adding 2.15 to both sides of the equation to eliminate the constant term:
0.2x - 2.15 + 2.15 = -8/27 + 2.15
0.2x = -8/27 + 2.15
Step 2: To simplify the right side of the equation, find a common denominator. The least common denominator between 27 and 1 is 27. Rewrite the fractions:
0.2x = (-8/27) + (2.15 * 27/27)
0.2x = -8/27 + 57.85/27
Step 3: Combine the fractions on the right side of the equation:
0.2x = (-8 + 57.85)/27
0.2x = 49.85/27
Step 4: To solve for x, divide both sides of the equation by 0.2:
x = (49.85/27) / 0.2
x = (49.85/27) * (1/0.2)
x = (49.85/27) * 5
Step 5: Simplify the result:
x ≈ 9.240
NOPE
Apologies for the incorrect response. Let's solve the equation correctly:
To solve 0.2x - 2.15 = -8/27, you can follow these steps:
Step 1: Start by adding 2.15 to both sides of the equation to eliminate the constant term:
0.2x - 2.15 + 2.15 = -8/27 + 2.15
0.2x = -8/27 + 2.15
Step 2: To simplify the right side of the equation, find a common denominator. The least common denominator between 27 and 1 is 27. Rewrite the fractions:
0.2x = (-8/27) + (2.15 * 27/27)
0.2x = -8/27 + 57.85/27
Step 3: Combine the fractions on the right side of the equation:
0.2x = (-8 + 57.85)/27
0.2x = 49.85/27
Step 4: To solve for x, divide both sides of the equation by 0.2:
x = (49.85/27) / 0.2
x = (49.85/27) * (1/0.2)
x = (49.85/27) * 5/1
Step 5: Simplify the result:
x ≈ 9.240
So, the solution to the equation is x ≈ 9.240.
To solve 0.2x - 2.15 = -8/27, you can follow these steps:
Step 1: Start by adding 2.15 to both sides of the equation to eliminate the constant term:
0.2x - 2.15 + 2.15 = -8/27 + 2.15
0.2x = -8/27 + 2.15
Step 2: To simplify the right side of the equation, find a common denominator. The least common denominator between 27 and 1 is 27. Rewrite the fractions:
0.2x = (-8/27) + (2.15 * 27/27)
0.2x = -8/27 + 57.85/27
Step 3: Combine the fractions on the right side of the equation:
0.2x = (-8 + 57.85)/27
0.2x = 49.85/27
Step 4: To solve for x, divide both sides of the equation by 0.2:
x = (49.85/27) / 0.2
x = (49.85/27) * (1/0.2)
x = (49.85/27) * 5/1
Step 5: Simplify the result:
x ≈ 9.240
So, the solution to the equation is x ≈ 9.240.
change the 8/27 to 8.27
mb
mb
To solve 0.2x - 2.15 = 8.27, you can follow these steps:
Step 1: Start by adding 2.15 to both sides of the equation to eliminate the constant term:
0.2x - 2.15 + 2.15 = 8.27 + 2.15
0.2x = 10.42
Step 2: To solve for x, divide both sides of the equation by 0.2:
x = 10.42 / 0.2
x = 52.1
So, the solution to the equation is x = 52.1.
Step 1: Start by adding 2.15 to both sides of the equation to eliminate the constant term:
0.2x - 2.15 + 2.15 = 8.27 + 2.15
0.2x = 10.42
Step 2: To solve for x, divide both sides of the equation by 0.2:
x = 10.42 / 0.2
x = 52.1
So, the solution to the equation is x = 52.1.